Current Progress in Tonoplast Proteomics Reveals Insights into the Function of the Large Central Vacuole - Trentmann, Oliver; Haferkamp, Ilka (Frontiers in Plant Science, 2013)
Vacuoles of plants fulfill various biologically important functions, like turgor generation and maintenance, detoxification, solute sequestration or protein storage. Different types of plant vacuoles (lytic vs. protein storage) are characterized by different functional properties apparently caused by a different composition/abundance and regulation of transport proteins in the surrounding membrane, the tonoplast. Proteome analyses allow the identification of vacuolar proteins and provide an informative basis for assigning observed transport processes to specific carriers or channels. This review summarizes techniques required for vacuolar proteome analyses, like e.g. isolation of the large central vacuole or tonoplast membrane purification. Moreover, an overview about diverse published vacuolar proteome studies is provided. It becomes evident that qualitative proteomes from different plant species represent just the tip of the iceberg. During the past few years, mass spectrometry achieved immense improvement concerning its accuracy, sensitivity and application. As a consequence, modern tonoplast proteome approaches are suited for detecting alterations in membrane protein abundance in response to changing environmental/physiological conditions and help to clarify the regulation of tonoplast transport processes.